To all men and women of good will (leaflet) - Haldane, Charlotte Franken, 1894-1969 (1937)
016a_0001_001 INTERNATIONAL BRIGADE Dependents and Wounded Aid Committee PATRONS: The Duchess of Atholl, M.P. Oliver Harris Ald. J. Reeves H.N. Brailsford Will Lawther E. Shinwell, M.P. Seymour Cocks, M.P. Earl of Listowel W.J.R. Squance J.B. Priestley Ebby Edwards Eleanor Rathbone, M.P. G.R. Strauss. M.P. Prof. J.B.S. Haldane, F.R.S. Wilford Roberts M.P. Ellen Wilkinson, M.P. To all Men and Women of Good Will Thousands of men from 32 countries have given up everything, many their lives, in the defence of world democracy and peace in Spain. Amongst them are one thousand men from the British Isles, who left before the ban on volunteers. The great debt we owe them can be in part, at least, repaid, by taking care that those they left behind — mothers, wives, children, and other dependents — do not suffer through the departure of their breadwinner to fight and to defeat Fascist aggression. £700 IS NEEDED EACH WEEK TO ASSIST DEPENDENTS AND TO PROVIDE CONVALESCENCE AND CARE FOR THE WOUNDED. We cannot replace those who have fallen, but we are doing our utmost to ensure that not a mother nor a child shall suffer materially for their loss. We ask for your support of this humane work. The Dependents' and Wounded Aid Committee, CHARLOTTE HALDANE, Hon. Sec. 1, Litchfield Street, W.C.2. M.P.C. (T.U.) E.C.1. 292/946/16a/1